Defect minimized Ag-ZnO microneedles for photocatalysis - Sanjay Gopal Ullattil (4899919) (2020)
A facile solution processing strategy has been developed for the formation of Ag-modified ZnO microneedles at various calcination temperatures such as 300, 500, and 700 °C (AZ3, AZ5, and AZ7 respectively). Due to the heavy doping of AgNO3, Ag+ ions have been incorporated in to the crystal lattice of ZnO in all the Ag-ZnO samples, which facilitated the formation of Ag-ZnO microneedle morphology with minimized defect states, and obviously, the plasmon peaks were observed due to Ag modification. These Ag-ZnO microneedle structures have been evaluated for their photocatalytic performance using methylene blue as model target contaminant and their activity was compared with the commercially available titania P25 photocatalyst. The photoactivity of all the Ag-ZnO microneedle structures was significantly higher than that of the commercially available P25 photocatalyst with the most active Ag-ZnO material having a photocatalytic activity ~ 1.4 times greater than that of P25 titania. Other Information Published in: Environmental Science and Pollution Research License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s11356-020-09433-5